PENGARUH FAKTOR EKONOMI TERHADAP TINGKAT KEKERASAN TERHADAP PEREMPUAN DI INDONESIA - Saputra, Muhammad Ari (Journal of Law ( Jurnal Ilmu Hukum ), 2025)
ABSTRACT.Economic pressure, income instability, and high levels of poverty are believed to be triggers of tension in households, which can then lead to acts of violence. This research examines the impact of economic factors on the high rates of violence against women in Indonesia and the legal protection against violence towards women. This study employs normative research, which is also defined as library legal research using various literature as study materials and analytical resources. The influence of economic factors on the high levels of violence against women in Indonesia is complex and significant. Financial instability, women's economic dependence on partners, and economic inequality within households all contribute to the rising risk of violence against women. Legal protection for women who are victims of violence in Indonesia is regulated by laws, such as the Domestic Violence Law and Human Rights Law. By providing skills training, access to business credit, and other economic support, women can become more financially independent and have options to escape violent situations. Keywords: Economy, Violence Against Women.